Finding Loopholes in Sanctions: Effects of Sanctions on North Korea's Refined Oil Prices - Kyoochul Kim (KDI Journal of Economic Policy, 2020)
The international community's sanctions against North Korea, triggered by North Korea's nuclear tests and by missile development in the country, are considered the strongest sanctions in history, banning exports of North Korea's major items and limiting imports of machinery and oil products. Accordingly, North Korea's trade volume decreased to the level of collapse after the sanctions, meaning that the sanctions against North Korea were considered to be effective. However, according to this paper, which analyzed the price fluctuations of refined petroleum products in North Korea through the methodology of an event study, the market prices of oil products were only temporarily affected by the sanctions and remained stable over the long run despite the restrictions on the volumes of refined petroleum products introduced. This can be explained by evidence that North Korea has introduced refined oil supplies that are not much different from those before the sanctions through its use of illegal transshipments even after the sanctions. With regard to strategic materials such as refined oil, the North Korean authorities are believed to be desperately avoiding sanctions by, for instance, finding loopholes in the sanctions to meet the minimum level of demand.
Keywords: F51; P22; P37; 330; North Korean Economy; Economic Sanctions; Smuggling; Refined Oil Prices; Illegal Transshipment